MUNINN LIBRARY Â€“ A VIRTUAL GAMIFIED LIBRARY - Santos, João Victor Guimarães; Debastiani, Eduardo Zoldan; Debastiani, Daniel Araujo; Silva, João Vàtor Luiz Soares; Santiago, Lucas Oliveira; Rosa, Luis Felipe Borges; Lima, Rafael Luiz Pires (CIPEEX, 2022)
ACCORDING TO THE 5TH EDITION OF THE "PORTRAITS OF READING" SURVEY IN BRAZIL, IT SUSTAINED A SIGNIFICANT DROP OF APPROXIMATELY 4.6 MILLION READERS IN BRAZIL BETWEEN 2015 AND 2019. WITH THE RECENT DECLINE IN THE NUMBER OF ACTIVE READERS IN BRAZILIAN TERRITORY, DUE TO LACK OF TIME, OR INTEREST, THERE IS A COMMON PROBLEM. OFTEN THE INDIVIDUAL INTENDS TO READ BUT GIVES UP ON THE WAY BECAUSE HE DOES NOT FIND VIABLE SOURCES OR SPENDS A LOT OF TIME OR MONEY WHENEVER HE WANTS TO FIND AND PURCHASE A BOOK, WHETHER PHYSICAL OR VIRTUAL. GIVEN THIS PREROGATIVE, THE MUNINN INITIATIVE HAS AS ITS MAIN OBJECTIVE TO FACILITATE AND MAKE READING CONVENIENT WITH THE APPLICATION OF EFFICIENT RESEARCH METHODS, SO THAT THE USER RESERVES HIS TIME TO READ AND DOES NOT HAVE TO SHARE IT WITH THE SEARCH FOR ITS CONTENT. IN ADDITION TO READING BOOKS, IT ALSO SPENDS ITS TIME IN ITS REVIEWS WITH OTHER USERS, BEING ABLE TO STORE THE ONES THAT THE USER ALREADY HAS OUTSIDE THE PLATFORM, TO CONCENTRATE ALL THE CONTENT IN ONE PLACE. IN THE DEVELOPMENT OF THE SOFTWARE, THE SCRUM METHOD WILL BE USED, WITH A FOCUS ON THE MVP OF THE PRODUCT, CREATED THROUGH USER STORIES AND TEAM GOALS. FOR THE CHOICE OF THE FUNCTIONALITY TO BE DEVELOPED IN THE WEEK SPRINT, THE ORDER OF PRIORITY AND THE LEVEL OF DIFFICULTY, DEFINED THROUGH PLANNING POKER, WILL BE TAKEN INTO ACCOUNT. MUNINN'S VISUAL IDENTITY WAS DESIGNED TO APPEAL TO THE USER'S COGNITION AND BE INTUITIVE IN ITS FEATURES, AND ITS DEFINITION WAS MADE THROUGH THE ANALYSIS OF PERSONAS. THE COLORS HAVE LOW SATURATION AND WARM TONES, SO THE EYES FEEL MORE RESTED, FOLLOWING THE PRINCIPLES OF COLOR PSYCHOLOGY. THE BLOCK STRUCTURE OF THE PAGE MAKES IT EASIER FOR THE BRAIN TO UNDERSTAND THE SHAPES, BEING ABLE TO UNDERSTAND THE INTERFACE WITHOUT MUCH EFFORT, FOLLOWING THE GESTALT LAW. SOME ELEMENTS, SUCH AS BOOK COVERS OR DETAILED DESCRIPTIONS, MAY APPEAR PARTIALLY COVERED IN THE INTERFACE, INDICATING THE IDEA OF CONTINUATION, THUS APPLYING THE UX RULE. THE DIGITAL READER SCREEN HAS ELEMENTS THAT CAN BE HIDDEN FROM THE INTERFACE, FOR FULL FOCUS WHEN READING. THE RESULTS ACHIEVED WERE THE FIRST SCREENS OF THE SITE: THE PROFILE, HOME, AND DIGITAL READER PAGES WERE PROTOTYPED USING THE FIGMA PLATFORM, DEMONSTRATING THE ARRANGEMENT OF ELEMENTS, HOW THE RULES WILL BE APPLIED, AND THE INITIAL LOOK OF THE PLATFORM.